A Macroergonomic Usability Evaluation of Pre-filled Medication Syringes. Issue 1 (June 2014) - Yang, Yushi; Rivera, A. Joy; Fortier, Christopher; Abernathy, James
Anesthesia providers experience high workload in the Operating Room (OR) environment due to the complex process of the self-filled medication syringes (SFS) medication preparation and administration. Improvements have been continuously made in order to ensure the safety of anesthesia medication management processes. One proposed way is to replace SFS with pre-filled medication syringes (PFS). This implementation is still in its infancy, therefore, there are opportunities to improve the design of PFS and facilitate their compatibility within the overall work system. This research took a macroergonomic perspective to examine the interactions end-users' have with PFS within the working context. The purpose was to identify PFS' usability problems and their potential effects on the anesthesia medication management process. Two human factors engineers conducted 27-hours of observation. Data was aggregated into three storyboard-style scenarios that described the prominent system vulnerabilities that exist when PFS are used. Based on the scenarios, design recommendations were proposed that enhance medication management safety and efficiency of workflow. It is concluded that while PFS are considerably more beneficial with respect to patient safety and providers' workflow, they may introduce new unintended complications that need to be addressed.